HUBUNGAN TINGKAT PENGETAHUAN DENGAN PENERAPAN SELF CARE PASIEN DIABETES MELLITUS TIPE II - Febtian Cendradevi Nugroho; Emiliandry Febryanti Tafin Banase (Nursing Arts, 2022)
ABSTRACT The self-care ability of diabetes mellitus patients is very important to maintain a high quality of life. A good self-care or self-management could prevent complications, thus, patient needs knowledge about it. The level of Knowledge plays an important role for diabetes mellitus patients because it relates to their quality of life. This study provides an overview of the relationship between knowledge level and self-care in Type II Diabetes Mellitus patients. This research used quantitative with cross-sectional method. The population of the study were type II diabetes mellitus patients who were stay at the area of ​​the Oesapa Health Center, Kupang City, with a sample of 80 people using a probability sampling technique with a simple random sampling type. The research instrument used the Diabetes Knowledge Questionnaire (DKQ) questionnaire and self-care activity sheets. Based on the results of the chi-square test, p-value of 0.395 ≥ 0.05 was obtained. It means that there is no relationship between Knowledge Level and Self-Care of Diabetes Mellitus Patients in the working area of ​​the Oesapa Health Center, Kupang City.